Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Kopi Bubuk Banyuatis di Kota Denpasar - TAMPUBOLON, MAYSARA; ANTARA, MADE; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Factors that Influence the Decision to Purchase the Banyuatis Powder Coffee in Denpasar City The purchase decision is the act of the consumer buying a product or an item provided by a store. Consumers are influenced by information about products, prices, distribution, and promotion. In these conditions, the decision to choose a brand contributes to a modern lifestyle, so the desire to buy branded products also colors one's consumption pattern. For that, business people must know what factors are taken into consideration by consumers in making purchasing decisions. The sample studied was 85 respondents from the total unknown population with the sampling method used was accidental sampling. The primary data werecollected through interviews and questionnaires while secondary data weregathered from books and scientific documents; the method used in this study was descriptive analysis and SEM-PLS analysis. Descriptive analysis results were that Banyuatis products were based on packaging and variation; prices based on the weight of coffee sold, prices based on the type of coffee and prices based on coffee packaging; distribution is based on the type of coffee and coffee packaging, namely regular and premium, where regular distributed products are dominant in minimarkets and traditional stalls while premium products are distributed predominantly in gift shops, cafes and hotels; promotions include advertising, personal sales, sales promotions, and public relations. SEM-PLS analysis can be concluded that the product (X1), price (X2), distribution (X3), promotion (X4), and brand image (X5) had a positive and significant effect on purchasing decisions (Y) Banyuatis Powder Coffee. It is recommended that the Banyuatis Powder Coffee Company should continue to improve the quality in terms of product, price, promotion, distribution, and brand image to help improve purchasing decisions.